2020
DOI: 10.1186/s12964-020-00664-0
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin- and dynamin-dependent endocytosis limits canonical NF-κB signaling triggered by lymphotoxin β receptor

Abstract: Background Lymphotoxin β receptor (LTβR) is a member of tumor necrosis factor receptor (TNFR) superfamily which regulates the immune response. At the cellular level, upon ligand binding, the receptor activates the pro-inflammatory NF-κB and AP-1 pathways. Yet, the intracellular distribution of LTβR, the routes of its endocytosis and their connection to the signaling activation are not characterized. Here, we investigated the contribution of LTβR internalization to its signaling potential. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…It can be speculated that these receptors regulate the immune response during infection. Predictably, the same set of host receptors was involved in the clathrin‐related endocytosis process (Appendix Fig S8 ), which is activated during the internalization of a large number of viruses (e.g., influenza virus, SARS coronavirus, Hepatitis B virus) (Brodsky et al , 1992 ; Veiga & Cossart, 2006 ; Maksymowicz et al , 2020 ). Moreover, domain‐based enrichment analysis showed that adaptin domains were overrepresented in the interactomes of several receptors (TOP3B, CLEC4D, CLEC4E, TMPRSS2, IFITM1, IFITM3), indicating their roles in cellular trafficking (Appendix Fig S9 ).…”
Section: Resultsmentioning
confidence: 99%
“…It can be speculated that these receptors regulate the immune response during infection. Predictably, the same set of host receptors was involved in the clathrin‐related endocytosis process (Appendix Fig S8 ), which is activated during the internalization of a large number of viruses (e.g., influenza virus, SARS coronavirus, Hepatitis B virus) (Brodsky et al , 1992 ; Veiga & Cossart, 2006 ; Maksymowicz et al , 2020 ). Moreover, domain‐based enrichment analysis showed that adaptin domains were overrepresented in the interactomes of several receptors (TOP3B, CLEC4D, CLEC4E, TMPRSS2, IFITM1, IFITM3), indicating their roles in cellular trafficking (Appendix Fig S9 ).…”
Section: Resultsmentioning
confidence: 99%
“… 205 CRISPR-Cas9 is a novel efficient method for gene knockout and involves the Cas9 protein, an enzyme responsible for DNA cutting and a single guided RNA (sgRNA), which guides Cas9 to a specific location in the DNA sequence. 204,205 This approach has been used to prepare AP2M1, 206 CAV1, 207 dynamin 208 and Rac 209 knockout cells. Patel et al , studied the intracellular delivery of mRNA from lipid NPs.…”
Section: Methods To Study Endocytosismentioning
confidence: 99%
“…It is possible that lack of Pm AP2-β may impair clathrin-mediated endocytosis, resulting in alteration of signaling. It was previously reported that clathrin and dynamin-deficient cells showed enhanced activation of canonical NF-κB signaling 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of endocytosis and endosomal sorting results in increased LPS signaling. In addition, the impairment of clathrin internalization enhances expression of lymphotoxin β receptor (LTβR) and activation of canonical NF-κB signaling 25 . These evidences suggest that clathrin-dependent endocytosis could regulate several signaling pathways.…”
Section: Introductionmentioning
confidence: 99%